Detect and Mitigate Blockchain-Based DDoS Attacks Using Machine Learning and Smart Contracts (Informatica, 2022)
The key target of Distributed Denial-of-Service (DDoS) attacks is to interrupt and suspend any available online services either executed for professional or personal gains. These attacks originate from the fast advancement in the number of insecure technologies. The attacks are caused due to the easy access to internet and advent of technology resulting to exponential growth of traffic volumes. DDoS attack remains most leading security risks to provisioning services. Also, the current embraced security mechanism for defense lacks flexibility and adequate resources to combat these attacks. Hence, there is need to embrace various other critical resources, where they can share the problem of mitigation. In addition, emerging technologies for instance smart contracts and blockchain offers for the sharing of these potential attacks information in an entirely automated and distributed manner. This paper recommends for a blockchain design which combines smart contracts and Machine Learning (ML) technologies, by presenting new ideal opportunities towards efficient DDoS mitigation solutions in variety of cooperative domains. Furthermore, the key advantage and benefits of this structure is deployment of still existing distributed and public infrastructure to blacklisted IP address or even advertise white, and the application of such an infrastructure with further defense mechanisms to current attacks of DDoS, deprived of considering distribution mechanisms or specialized registries, which facilitates the implementation of procedures across diverse domains. This paper further presents the demonstration and implementation features of this blockchain structure, discussion and study findings over these smart contracts and ML technologies. The study further concludes by recommending use of smart contract in collaborative block-chain design with ML for mitigating future attack of DDoS.